Male Teacher Assignment and Teacher Turnover in Elementary Schools - NaYoung Hwang; Brian Fitzpatrick (SAGE Publishing, 2021)
Parents and educators commonly assume that male teachers serve as more effective disciplinarians for boys than female teachers. Do schools tend to assign male teachers to teach boys with perceived behavioral issues? Our study uses administrative data in Indiana to investigate male teacher assignment in elementary school. We find that boys with at least one suspension record in the previous year are 12% more likely to be assigned to a male teacher than boys without suspensions, whereas girls' suspension histories do not predict assignments to male teachers. In addition, teachers who have 10% or more of students with suspension histories are 19.5% more likely to migrate to another school and 16.2% more likely to leave the state's teacher workforce. Our study suggests that male teachers have an elevated risk of being assigned to teach male students with suspension histories, which may contribute to teacher turnover.